A 'new (ab)normal'?: Scrutinising the work-life balance of academics under lockdown. Issue 9 (21st October 2021) - Ashencaen Crabtree, Sara; Esteves, Luciana; Hemingway, Ann
ABSTRACT: In March 2020 virtually all UK universities were suddenly thrown into an unprecedented and sudden closure of campus and facilities owing to the British Government's Covid-19 pandemic lockdown policies. Further evidence suggests that this exacerbated existing gendered differences. This paper reports on UK academic responses from an international survey examining the work-life balance of academics under Covid-19 lockdown. The aim of the study was to examine the experiences and perceptions of academics, using these to inform how universities can improve the work-life balance of academics during the current and post-lockdown scenarios, as well as in the longer term, given a pandemic-prone future. Rich in qualitative comments, primarily derived from women academics, gendered contrasts in work-life balance appear magnified under conditions of lockdown. Key lessons for HE internationally emerge from the findings.